Performance of novel free-breathing grasp reconstructions techniques in the identification of liver structures and lesions in a clinical population - Missima, Nathalia Guarienti (2020)
There is a huge demand for the development and validation of new techniques and sequences for MRI scanning, that can be fast, robust, with high spatial and temporal resolution, radiation-free, in order to improve MRI scanner use. This thesis had the collaboration of an international and multidisciplinary team, composed by engineers, physics and radiologists, to combine the last technologic MRI advances to the clinical practice. We intend to evaluate the accuracy and performance of respiratory-weighted (RW) and coil unstreaking (CUN) golden angle radial sparse parallel (GRASP) techniques against the original GRASP technique in a clinical population of patients with liver lesions.